2013
DOI: 10.1111/cch.12029
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the impact of regular use of the Wii Fit to improve motor and psychosocial outcomes in children with movement difficulties: a pilot study

Abstract: This study provides preliminary evidence to support the use of the Wii Fit within therapeutic programmes for children with movement difficulties. This simple, popular intervention represents a plausible method to support children's motor and psychosocial development. It is not possible from our data to say which children are most likely to benefit from such a programme and particularly what the dose and duration should be. Further research is required to inform across these and other questions regarding the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2
38

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(151 citation statements)
references
References 51 publications
(42 reference statements)
3
108
2
38
Order By: Relevance
“…Hence there may be enough underlying similarity between the AVGs and real world tasks to allow for some transfer of learning and development of gross motor skills. This is supported by previous studies demonstrating that balance training on the Wii Fit (Nintendo, Kyoto, Japan) device could improve balance performance in people with impaired balance and cerebral palsy (Hammond, Jones, Hill, Green, & Male, 2014;D. Jelsma, et al, 2014;J.…”
Section: Discussionsupporting
confidence: 83%
“…Hence there may be enough underlying similarity between the AVGs and real world tasks to allow for some transfer of learning and development of gross motor skills. This is supported by previous studies demonstrating that balance training on the Wii Fit (Nintendo, Kyoto, Japan) device could improve balance performance in people with impaired balance and cerebral palsy (Hammond, Jones, Hill, Green, & Male, 2014;D. Jelsma, et al, 2014;J.…”
Section: Discussionsupporting
confidence: 83%
“…Increased compliance by children to physical therapy using virtual reality has been reported (Levac & Miller, 2013) and it may be particularly beneficial for children with DCD as it does not require them to perform in front of other children (Straker et al, 2011). Several recent studies have confirmed that AVG therapy may enhance motor skill performance in populations with DCD (Hammond, Jones, Hill, Green, & Male, 2014;Jelsma et al, 2013;Salem et al, 2012). While one study Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There was a great number of studies that have investigated AVGs participation in PA and its positive effects in reducing the risk of obesity (e.g., Maloney, Threlkeld, & Cook, 2012;Goersch et al, 2013), hypertension (e.g., Chen & Wilkosz, 2014), congestive heart failure (e.g., Klompstra, Jaarsma, & Strömberg, 2014;Tripette et al, 2014), atherosclerosis (e.g., Laufer, Dar, & Kodesh, 2014) and cardiovascular disease (e.g., Thompson, Gordon, & Pescatello, 2010). Controlled studies also showed that active video games increased capacities in relation to PA and education (Hammond, Jones, Hill, Green, & Male, 2014). Similarly, previous research has indicated that AVGs have an assortment of positive effects (Heidi et al, 2014) such as an increased moderate-vigorous physical activity (Biddiss, & Irwin, 2010), a decreased light activity (Lu, Kharrazi, Gharghab, & Thompson, 2013), a modest increase in sedentary screen time (Papastergiou, 2009) and a post-intervention energy compensation (LeBlanc et al, 2013;Peng et al, 2014).…”
Section: Discussionmentioning
confidence: 82%